ANALISIS PERAMALAN PERMINTAAN PRODUK NATA DE COCO UNTUK MENDUKUNG PERENCANAAN DAN PENGENDALIAN PRODUKSI DALAM SUPPLY CHAIN DENGAN MODEL CPFR (COLLABORATIVE PLANNING, FORECASTING, AND REPLENISHMENT) - Saptaria, Lina (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2017)
Effective business process strategy in the application of SCM (Supply Chain Management) is the use of collaborative planning, forecasting and replenishment (CPFR) methods where producers, distributors and retailers work together to plan, forecast and fill return products sold in the market. The purpose of this study is to describe the process of preparing collaborative forecasting between Supply Chain partners by referring to the CPFR model workflow in micro-scale manufacturing business and finding the most effective and efficient forecasting methodology that can be used as the basis for decision making in planning and production control throughout the supply chain. Forecasting analysis using time series model with 3 methods of Moving Averages with 4 month time period, Trend Projection exponential smoothing method with α = 0.1, α = 0.5, α = 0.9 and Linear Regression (Least Squares). The results show that the Linear Regression (Least Squares) method is the most effective method that can be used as the basis for decision making in production planning and control throughout the supply chain. Keywords: Demand Forecasting, Production Planning and Control, Time Series Method, CPFR Model